Computer Network Security: Challenges, Threats, and Protection Strategies in the Digital Era - Rayyan Faris Muhammad; Ilma Nafi’atu Qorien; Ling Bachtiar (PT Mekar Research and Publishing, 2026)
Over the past few decades, rapid advances in information technology have brought about significant changes in the way people interact, communicate, and manage data. Conversely, these advancements have been accompanied by an increase in threats to computer network security. In this article, we will explore various aspects of computer network security, ranging from the most common types of threats, available protection technologies, to methods for successfully implementing security systems. This study collects, analyzes, and synthesizes various relevant scientific sources from Indonesian national journals published over the past five years (2021–2025). The findings indicate that cyber threats such as DDoS attacks, malware, brute force attacks, and SQL injection are increasingly prevalent, necessitating a layered approach to building network security systems. In the contemporary network security ecosystem, firewalls, intrusion detection systems (IDS), intrusion prevention systems (IPS), Virtual Private Networks (VPN), data encryption, and penetration testing are essential. The conclusion of this article is that network security is not a product, but a process that must be updated and adapted in line with the evolution of cyber threats.